Effectiveness and Efficiency of Peripheral Nerve Blocks as Adjunct to General Anaesthesia for Open Reduction and Internal Fixation Surgery at Primary Hospital in Tangerang - Ramadhan, Yoga; Sari, Wilujeng Puja; Setiawan, Andy (JAI (Jurnal Anestesiologi Indonesia), 2025)
Background: Pain management is essential for postoperative patients. Effective management involves considerations such as the type of Anesthesia. It affects the total cost of spent, quality of pain control, and side effects. This study will evaluate the addition of peripheral nerve blocks (PNB) in orthopedic surgery patients.Objective: The objective of this study is to evaluate the efficacy and efficiency of PNB as an adjunct in general anesthesia (GA). Variables to be assessed the total cost of drugs, pain score and side effects after surgery.Methods: This study is an analytic study with a case-control approach that includes 116 patients. Secondary data were obtained through patient medical record data. Data in the form of types of anesthesia, total cost of drugs used before and 24 hours after surgery, pain scale before and during 24 hours after surgery and side effects in patients.The samples were divided into two groups: the GA group and the GA with PNB (GA-PNB) group. The intensity of pain was evaluated by a numeric rating scale. The total cost was calculated based on the drugs administered prior to and within 24 hours after surgery. The assessment of side effects was converted into scores to the following criteria: 0 = no symptoms, 1 = one symptom, and 2 = multiple symptoms.Result: The results showed that the total cost of drugs spent for GA-PNB group was 18.3% less than GA group. GA-PNB produces lower pain scores and lower incidence of side effects. The average pain scale in GA patients was 3.8 points and GA with PNB was 2.8 points.Conclusion: The addition of PNB has the potential to improve patient satisfaction. Lower pain scores, lower side effects and lower costs will encourage patients to choose Primaya Hospital Pasar Kemis for their treatment.